Studium przypadku dyglosji językowej w języku pundżabskim i zmiany językowej w prowincji Beludżystan - Alizai, Kinza (Pedagogika Społeczna Nova, 2021)
Language shift is a social phenomenon where one language substitutes another. In the social phe- nomenon of language attrition strong reasons are needed to enable the action such as environmental, social, political, economical and geographical changes. Proposed study detects Language Shift of Pun- jabi speech community which is the permanent settler of the Baluchistan province. Punjabi speakers, also being to a minority ethnic community are disinclined to articulate/accept their linguistic, ethnic and geographic identity. By this vein, the study aims to explore the social as well as political factors that are the pavestones for this linguistic and ethnic shift of Punjabi speakers. The study is qualitative in nature as the data was collected via semi-structured interview. The data is collected form 25 interviewees by executing the purposeful sampling means. The recorded interviews were transcribed and assigned codes by applying the technique of thematic analysis. The results have shown that the local communi- ties, other than Punjabi (e.g., Pushto, Balochi and Brahui) have negative attitudes for Punjabi language due to various historical, political events such as Army operations and state prejudice in which Punjab and federal government played key role. As a result, Punjabi language suffered the badly and expe- rienced a drastic linguistic drop. Regardless of age, whole speech community is weighed down with a causal danger and threat of being labeled and stigmatized in general arena. Social bigotry and intol- erance of Baluchistan’s local speech communities towards the Punjabi speech community resulted in language shift/attrition or less fluent speakers of Punjabi language.